Psychosocial predictors of nonadherence to medical management among patients on maintenance dialysis - Alosaimi FD (International Journal of Nephrology and Renovascular Disease, 2016)
Fahad Dakheel Alosaimi,1 Mohammed Asiri,2 Saleh Alsuwayt,2 Tariq Alotaibi,2 Mohammed Bin Mugren,2 Abdulmalik Almufarrih,2 Saad Almodameg,2 1Department of Psychiatry, King Saud University, Riyadh, Saudi Arabia; 2College of Medicine, King Saud University, Riyadh, Saudi Arabia Background: A number of reports suggest a link between depression and nonadherence to recommended management for end-stage renal disease (ESRD) patients on maintenance dialysis. However, the relationship between nonadherence and other psychosocial factors have been inadequately examined. Objectives: To examine the prevalence of psychosocial factors including depression, anxiety, insecure attachment style, as well as cognitive impairment and their associations with adherence to recommended management of ESRD. Methods: A cross-sectional observational study was carried out from 2014 to 2015. Chronic dialysis patients were recruited conveniently from four major dialysis units in Riyadh, Saudi Arabia. Nonadherence was defined as decreased attendance in dialysis sessions, failure to take prescribed medications, and/or follow food/fluid restrictions and exercise recommendations. Results: A total of 234 patients (147 males and 87 females) were included in this analysis, with 45 patients (19.2%) considered as nonadherent (visual analog scale < 8). Approximately 17.9% of the patients had depression (Patient Health Questionnaire score ≥10), 13.2% had anxiety (Hospital Anxiety and Depression scale-anxiety >7), while 77.4% had cognitive impairment (Montreal Cognitive Assessment score <26). Nonadherence was significantly associated with depression and anxiety (p<0.001 for both) but not cognitive impairment (p=0.266). The Experiences in Close Relationships – Modified 16 (ECR-M16) scale score was 27.99±10.87 for insecure anxiety and 21.71±9.06 for insecure avoidance relationship, with nonadherence significantly associated with anxiety (p=0.001) but not avoidance (p=0.400). Conclusion: Nonadherence to different aspects of ESRD continues to be a serious problem among dialysis patients, and it is closely linked to depression and anxiety. The findings from this study reemphasize the importance of early detection and management of psychosocial ailments in these patients. Keywords: dialysis, nonadherence, depression, anxiety, Saudi Arabia